INSULINOMA: CONTEMPORARY STRATEGIES FOR DIAGNOSIS, CLINICAL PRESENTATION, AND MULTIMODAL TREATMENT OF PANCREATIC NEUROENDOCRINE INSULIN-SECRETING TUMORS - Konrad Strużek; Agnieszka Kwiatkowska; Ewelina Mączka; Wiktor Tracz; Patrycja Świercz; Kinga Teper; Sandra Khiralla-Gawlik; Aleksandra Anna Strzelecka; Aleksandra Ewa Basak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Insulinoma, though rare, represents the most frequent hormonally active neuroendocrine neoplasm of the pancreas, responsible for causing endogenous hypoglycemia. In over 90% of cases, it presents as a solitary, benign, well-defined tumor smaller than 2 cm. Despite the presence of typical clinical signs, diagnosis is often postponed due to nonspecific symptoms that may mimic neurological or psychiatric disorders. Objective: This review aims to provide an updated overview of diagnostic strategies and treatment options for insulinomas in adults, excluding those linked to MEN syndrome or von Hippel-Lindau disease, with particular focus on imaging modalities for tumor localization and therapeutic alternatives for unresectable or malignant lesions. Methods: We analyzed the effectiveness of various imaging techniques, including non-invasive modalities (ultrasound, CT, MRI) and invasive methods (endoscopic ultrasound [EUS], arterial stimulation with venous sampling [ASVS]), in detecting insulinomas. Surgical approaches were reviewed alongside minimally invasive options such as alcohol ablation, radiofrequency ablation (RFA), embolization, and medical therapies. Management strategies for malignant insulinomas were also examined, emphasizing the role of multimodal treatment, including chemoembolization and liver transplantation. Conclusions: Surgical removal remains the preferred treatment for most insulinomas, offering the possibility of complete remission. Precise preoperative localization greatly enhances surgical success and minimizes complications. In cases where resection is not feasible or in malignant disease, alternative therapies can help manage hypoglycemia and improve quality of life. Progress in imaging techniques and glucose monitoring is reshaping the diagnostic and therapeutic landscape for insulinoma.